The fatal flame - Faye, Lyndsay (Timothy Wilde mysteries, 2015)
Reluctantly embroiled in a 1840s dispute between a corrupt Tammany Hall leader and an arsonist with an agenda, Copper Star Timothy Wilde finds his investigation challenged by his brother's decision to run for public office.